Synergy between BMT and Cooperatives: A Sharia Financial Assistance Model to Increase the Business Scale of Ibu-Ibu PKK in Gintung Village, Sukadiri District - Sahroni; Ahmad Baizuri (International Research & Development for Human Beings (IRDH), 2025)
This research and community program emerged in response to limited access to Sharia-based capital and low financial literacy among PKK women, who are the backbone of the family economy and the main actors in micro-enterprises in the village. This program was conducted through a participatory seminar, which was systematically and interactively designed. Activities included presentations of Sharia economics and finance materials by experts, group discussions based on participants' focus problems, case studies of successful BMTs and Sharia Cooperatives, and a question-and-answer session. The results of the activity showed a 70–80% increase in participants' understanding of Islamic financial principles, particularly in business financial management, the separation of family and business finances, and an introduction to Islamic contracts such as murabahah and mudharabah. Group discussions generated concrete ideas that can be immediately implemented to strengthen micro-enterprises and increase the scale of family economies. In conclusion, this seminar demonstrated that a participatory approach through interactive education and case study discussions can effectively improve Islamic financial literacy. This activity also empowered the PKK women of Gintung Village, provided practical insights for business development, and served as a model of community service that can be replicated in other villages with similar characteristics.